Hubungan Kecerdasan Emosi dengan Kemampuan Coping Adaptif - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study was aimed to analyze the correlation between adaptive coping and emotional intelligence (El). The subject of this study (N=69) are high school students in SMU Negeri 8 Yogyakarta, whose age ranged from 15 to 17 years old. Adaptive coping is measured by adaptive coping scale, and E1 is measured by E1 scale. Researcher developed both scale. Data was analyzed using Pearson's product moment correlation. Results show that there are: positive correlation between E1 and problemfocused coping (PFC) part I (r=O,302